Subtitling Strategies and the Preservation of Satirical Implicatures in From the Ashes: The Pit - Maulida Az-Zahra; Moh Zawawi (Jurnal Bahasa dan Sastra, 2026)
Satirical utterances in audiovisual texts convey criticism through implicit meanings, rhetorical contrasts, and contextual cues, making them vulnerable to shifts in cross-cultural subtitling. This exploratory case study examines how Arabic satirical implicatures are preserved, reformulated, or weakened in the official Indonesian subtitles of From the Ashes: The Pit. The data comprised 23 satirical utterances identified through exhaustive criterion-based sampling of the entire film. The Arabic dialogue was manually transcribed, verified by an Arabic-language specialist, aligned with scene timestamps, and compared with the Indonesian subtitles. Analysis combined Gottlieb’s subtitling strategies, Simpson’s model of satirical discourse, Zabalbeascoa’s functional approach, Relevance Theory, and audiovisual constraints. Four strategies were identified: transfer (11), paraphrase (9), condensation (2), and resignation (1). The corpus included irony (10), cynicism (7), and sarcasm (6). The findings suggest that satirical implicatures were preserved when the subtitle retained the target of criticism, evaluative stance, and sufficient verbal or audiovisual cues. Paraphrase and condensation could also maintain satire when formal changes preserved these functional elements, whereas resignation produced the clearest contextual ambiguity. These findings are limited to this single-film exploratory corpus.